Czar hebanowych kształtów. Ciało pornograficzne w kontekście pornografii międzyrasowej = Magic of ebony shapes. Body of pornography in the contexts of interracial pornography - Małczyński, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Pornography is a kind of caricature of reality. But it also presents human diversity in the specific way. It uses racial stereotypes which are widely spread in the Euro-American culture. For example, it shows the black as dangerous animals seeking sexual contacts with the "dominant race". On the other hand, it portrays Asian females as the embodiment of sexual power of the Orient. Black or Asian actors play the roles which are to entertain a white spectator.
Keywords: pornografia; ciało ludzkie; rasa